2018
DOI: 10.1029/2018jc013949
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Circulation Changes in the Deep North Atlantic From 16°N and 26°N Transport Arrays

Abstract: The meridional overturning circulation (MOC) has been measured by boundary arrays in the Atlantic since 2000. Over the past decade of measurements, however, the reported tendencies in overturning circulation strength have differed between 16°N and 26°N. Here we investigate these differences by diagnosing their origin in the observed hydrography, finding that both arrays show deep waters (below 1,100 dbar) at the western boundary becoming fresher and less dense. The associated change in geopotential thickness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…Studies of meridional coherence based on observations showed an apparent lack of coherence even just within the North Atlantic subtropical gyre on seasonal timescales (Mielke et al, 2013;Elipot et al, 2014Elipot et al, , 2017, although there is some indication of coherence on interannual and longer timescales (Frajka-Williams et al, 2018). Numerical modeling studies and inverse approaches have shown that the coherence of AMOC variability may be distinct between latitudes with coherent variability within the South Atlantic (Kelly et al, 2014(Kelly et al, , 2016), yet a lack of coherence between gyres in the North Atlantic (Bingham et al, 2007;Lozier et al, 2010) with slower propagation of anomalies in the subpolar regions (Zhang, 2007).…”
Section: Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of meridional coherence based on observations showed an apparent lack of coherence even just within the North Atlantic subtropical gyre on seasonal timescales (Mielke et al, 2013;Elipot et al, 2014Elipot et al, , 2017, although there is some indication of coherence on interannual and longer timescales (Frajka-Williams et al, 2018). Numerical modeling studies and inverse approaches have shown that the coherence of AMOC variability may be distinct between latitudes with coherent variability within the South Atlantic (Kelly et al, 2014(Kelly et al, , 2016), yet a lack of coherence between gyres in the North Atlantic (Bingham et al, 2007;Lozier et al, 2010) with slower propagation of anomalies in the subpolar regions (Zhang, 2007).…”
Section: Regionsmentioning
confidence: 99%
“…From the 26 • N array, surprisingly large variability was observed on timescales from weeks to a decade (see Srokosz and Bryden, 2015 for a review). However, at two subtropical latitudes (26 • N and 16 • N) AMOC fluctuations were incoherent: declining at 26 • N (Smeed et al, 2014) and intensifying (Frajka-Williams et al, 2018) at 16 • N over 2004-2017. Additionally, much of the variability at 26 • N on seasonal to interannual timescales is dominated by wind forcing (Zhao and Johns, 2014;Pillar et al, 2016), contradicting the previous hypothesis that buoyancy forcing in subpolar regions drives AMOC variations (Kuhlbrodt et al, 2007). The OSNAP array (spanning latitudes from 53 • N to 60 • N) was deployed in 2014 to elucidate the relationship between buoyancy forcing and overturning.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to the boundary current arrays at 11 • S, pressure-equipped inverted echo sounders have been deployed at 300 and 500 m on the continental margins on each side of the basin since 2013 to enable comprehensive AMOC estimates at this latitude. Since 2000, a mooring array has been maintained at 16 • N that includes velocity measurements covering the DWBC east of Guadeloupe and additional geostrophic moorings measuring the deep flow between the continental slope and the mid-Atlantic ridge (Send et al, 2011;Frajka-Williams et al, 2018). The 16 • N and 11 • S arrays contribute to the AMOC observing system and can be used to investigate links between the subtropical North Atlantic array at 26.5 • N (RAPID/MOCHA/WBTS) and the South Atlantic array at 34.5 • S (SAMBA).…”
Section: Boundary Current Arraysmentioning
confidence: 99%
“…We do not address in detail the different aspects related to the TAV to keep the paper concise. Besides, recently, some good reviews about the observing system in the Tropical currents at the Brazilian continental slope [39,40], the Angola Current [41], and the deep flow between the continental slope and the mid-Atlantic ridge (see Figure 1; [42,43]). These arrays contribute to the AMOC observing system.…”
Section: Introductionmentioning
confidence: 99%